Propagation of Tsunami Waves Multi-Factor Spread Simulation Based on CA Model - Mohamed, E.Syed; Rajasekaran, S. (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
Tsunamis and their associated destruction have highlighted the need for real –time simulation system for accurately predicting wave spread. Such system would assist decision makers in their efforts to effectively contain potentially catastrophic event. The present work proposes a new model for spreading of waves based on two-dimensional cellular automata. This model introduces factors of propagation from diagonal and adjacent neighbor cells and includes, in a detailed form, the rate of wave spread. Further, the model is useful for both homogeneous and non-homogenous environments. Preliminary simulation results demonstrating the proposed scheme are presented. In this paper, some physically realistic ocean parameters have been considered.